Komisi Ombudsman Daerah dan Good Governance - Suparman Marzuki (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The establishing local ombudsman means establishing an institution which maybe an instrumen for inforcing society to control the state, not merely for the sake of the societyitsself, but for the sake of the survivel of especially local government and generally for state. If Indonesian government can create a good fondation for local autonomy, they will attain good prospect in the future coming.